ANTHROPOLOGICAL ANALYSIS IN THE DEVELOPMENT OF SHARIA FINANCIAL INSTITUTIONS: SOCIAL AND CULTURAL - Irfaida, Irfaida; Asnawi, Nur; Khasanah, Umrotul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2024)
Anthropological analysis provides a unique understanding of the complex world of contemporary finance by focusing on the diversity of forms taken by institutions, actors and practices in financial markets, especially analyzing the specificities of the local conditions in which these develop. The coevolution of culture and institutions plays an important role in facilitating financial development. When these aspects change simultaneously and in the same direction, it leads to successful modernization of the financial framework. However, deviations in their development paths can result in challenges in implementing effective financial development strategies. Comprehensive exploration of the social and cultural dimensions of Sharia financial institutions through an anthropological lens, aiming to enrich understanding of the complex interactions between culture, society and finance in the context of Islamic finance. The contribution that can be offered in this research is that Sharia financial institutions operate within a different legal and ethical framework based on Islamic principles, requiring an in-depth understanding of Islamic jurisprudence and financial regulations, aspects that may not be fully explored through traditional anthropological approaches that focus on social and cultural dynamics.